2015
DOI: 10.1016/j.bbagrm.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer cooperativity as a novel mechanism underlying the transcriptional regulation of E-cadherin during mesenchymal to epithelial transition

Abstract: Epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) highlight crucial steps during embryogenesis and tumorigenesis. Induction of dramatic changes in gene expression and cell features is reflected by modulation of Cdh1 (E-cadherin) expression. We show that Cdh1 activity during MET is governed by two enhancers at +7.8 kb and at +11.5 kb within intron 2 that are activated by binding of Grhl3 and Hnf4α, respectively. Recruitment of Grhl3 and Hnf4α to the enhancers is crucial for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 54 publications
(39 reference statements)
6
66
2
Order By: Relevance
“…Her2 tumors contain the smallest NR2A2 amounts. In mammary-glands, NR2A1 has been the object of few studies [7781], while no studies on NR2A2 are available. NR2A1 may have oncosuppressive properties [77], as it is down-regulated in mammary epithelial-cells undergoing epithelial-to-mesenchymal transition (EMT).…”
Section: Enigmatic-orphansmentioning
confidence: 99%
“…Her2 tumors contain the smallest NR2A2 amounts. In mammary-glands, NR2A1 has been the object of few studies [7781], while no studies on NR2A2 are available. NR2A1 may have oncosuppressive properties [77], as it is down-regulated in mammary epithelial-cells undergoing epithelial-to-mesenchymal transition (EMT).…”
Section: Enigmatic-orphansmentioning
confidence: 99%
“…human immortalization breast cell line (HMLE) [1,12], mouse inner medullar collecting duct (mIMCD-3) [5], primary keratinocytes or human immortalization keratinocytes (HaCat) [13], and nontumorigenic mouse mammary gland cell line (NmuMG) [14], Grhls may play some roles in regulating mesenchymal-epithelial transition under physiological conditions. Though Alotaibi et al [14] demonstrated that Grhl3 could also activate E-cadherin expression in the hepatoma carcinoma cells derived from mesoderm, it has not been reported the Grhl3 functions during mesoderm development. In fact, Grhl3 can act as an activator or repressor on the target genes [6,21].…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin, an essential molecule for the formation of adhesion junction, is critical to form the intercellular contacts and frequently downregulated in the later stage of tumorigenesis. Some previous studies indicated that Grainyhead family factors are the activators of E-cadherin in the physiological context [1,5,[12][13][14]. Since Grhl3 also represses the expression of some target genes [6], we hypothesized that Grhl3 may regulate cancer cell migration and invasion by the downregulation of E-cadherin.…”
Section: Introductionmentioning
confidence: 99%
“…Mammary gland ducts 17,19,20 Breast cancer [17][18][19][20][21] Colon and rectum 7 Colorectal cancer 23,24 Lining of the stomach 26 Gastric cancer 25,26 Oral epithelium 7 Oral squamous cell carcinoma 27 Liver ducts 45 Hepatocellular carcinoma 28 Renal epithelium 46 Clear cell renal cell carcinoma Skin cancer 32,33 Mammary gland ducts 37 Breast cancer [34][35][36] Lung airways 7 Lung cancer 37,38 Urinary bladder 44 ?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In contradiction to these findings, in a recent publication it was reported that GRHL3 positively regulates the expression of E-cadherin in lung cancer, which would be suggestive of a tumor suppressive function. 37 However, the authors of the latter report did not specify the subtype of lung cancer studied, so it is still possible that GRHL3 acts as a tumor suppressor in some types of lung cancer and fulfils a different function in other types of lung cancer.…”
mentioning
confidence: 99%